Frequência de ocorrência de doenças crônico-degenerativas em adultos com mais de 50 anos - Turi, Bruna Camilo [UNESP]; Codogno, Jamile Sanches [UNESP]; Fernandes, Romulo Araujo [UNESP]; Amaral, Sandra Lia do [UNESP]; Monteiro, Henrique Luiz [UNESP] (My University, 2010)
OBJECTIVE: Describe the prevalence of disease according to classifi cation of nutritional status and physical activity level in users of the Basic Health Unit in the city of Bauru. METHODS: Cross-sectional study involving 117 individuals of both sexes aged over 50 years. We analyzed clinical records of patients, a questionnaire to assess level of physical activity and weight and height were measured to determine nutritional status. Data analysis was performed after dividing the subjects into groups of physical activity, Active / Sedentary and classifi cation of nutritional status: Eutrophic / Obese. The chi-square test was used to analyze the existence of associations. RESULTS: Cardiovascular diseases were more frequent among patients (38.3%), followed by metabolic (28.3%), osteoarticular (25.9%) and tumor (1%). There was an association between higher number of injuries and less physical activity, where active individuals aff ected by four or more diseases were 22.2% versus 77.8% of the sedentary. Analyzing nutritional status and physical activity level, it was observed that increasing the occurrence of injuries was directly proportional to the increase in body mass index and physical inactivity. Among obese, sedentary individuals who had suff ered three or more diseases were 67.3% and 43.8% active. Among the eutrophic 29.4% were active against 18.8% of the sedentary. CONCLUSION: The prevalence of diseases in adults over 50 years is associated with clustering of risk factors like physical activity and nutritional status.

OBJETIVO: Descrever a prevalência de doenças segundo classifi cação do estado nutricional e nível de atividade física em usuários de Unidade Básica de Saúde, na cidade de Bauru. MÉTODOS: Estudo transversal envolvendo 117 indivíduos de ambos os sexos e com idade superior a 50 anos. Foram analisados prontuários clínicos dos pacientes, aplicado um questionário para verifi car o nível de atividade física e foram aferidos peso e estatura para classifi cação do estado nutricional. A análise dos dados foi realizada após divisão dos indivíduos em grupos de atividade física: Ativos / Sedentários e classifi cação do estado nutricional: Eutrófi cos / Obesos. O teste qui-quadrado foi utilizado para analisar existência de associações. RESULTADOS: As doenças cardiovasculares foram as mais frequentes entre os pacientes (38,3%), seguida de metabólicas (28,3%), osteoarticulares (25,9%) e tumorais (1%). Observou-se associação entre maior número de agravos e menor atividade física, onde, indivíduos ativos acometidos por quatro ou mais doenças foram 22,2% contra 77,8% dos sedentários. Analisando-se classifi cação do estado nutricional e nível de atividade física, foi observado que o aumento da ocorrência de agravos foi diretamente proporcional ao aumento do índice de massa corporal e à inatividade física. Entre obesos, os sedentários que apresentaram três ou mais agravos foram 67,3% e os ativos 43,8%. Já entre os eutrófi cos foram 29,4% ativos contra 18,8% dos sedentários. CONCLUSÃO: A prevalência de doenças em adultos com mais de 50 anos está associada à agregação de fatores de risco como a atividade física e estado nutricional.
Frequency of chronic diseases in adults with more than 50 years old
Keywords: Chronic disease; Exercise; Obesity; Doença crônica; Exercício físico; Obesidade